Generating Pennycress (Thlaspi arvense) Seed Triacylglycerols and Acetyl-Triacylglycerols Containing Medium-Chain Fatty Acids - Esfahanian, Maliheh; Nazarenus, Tara J.; Freund, Meghan M.; McIntosh, Gary; Phippen, Winthrop B.; Phippen, Mary E.; Durrett, Timothy P.; Cahoon, Edgar B.; Sedbrook, John C. (Frontiers in Energy Research, 2021)
Thlaspi arvense L. (pennycress) is a cold-tolerant Brassicaceae that produces large amounts of seeds rich in triacylglycerols and protein, making it an attractive target for domestication into an offseason oilseed cash cover crop. Pennycress is easily genetically transformed, enabling synthetic biology approaches to tailor oil properties for specific biofuel and industrial applications. To test the feasibility in pennycress of producing TAGs and acetyl-TAGs rich in medium-chain fatty acids (MCFAs; C6–C14) for industrial, biojet fuel and improved biodiesel applications, we generated transgenic lines with seed-specific expression of unique acyltransferase (LPAT and diacylglycerol acyltransferase) genes and thioesterase (FatB) genes isolated from Cuphea viscosissima, Cuphea avigera var. pulcherrima, Cuphea hookeriana, Coco nucifera, and Umbellularia californica. Wild-type pennycress seed TAGs accumulate no fatty acids shorter than 16C and less than 5 mol percent C16 as palmitic acid (16:0). Co-expressing UcFatB and CnLPAT produced up to 17 mol% accumulation of lauric acid (12:0) in seed TAGs, whereas CvFatB1 CvLPAT2 CpDGAT1 combinatorial expression produced up to 27 mol% medium chain FAs Medium Chain Fatty Acids mostly in the form of capric acid (10:0). CpFatB2 ChFatB2 combinatorial expression predominantly produced, in equal parts, up to 28 mol% myristic acid (14:0) and palmitic acid. Genetically crossing the combinatorial constructs into a fatty acid elongation1 (fae1) mutant that produced no 22:1 erucic acid, and with an Euonymus alatus diacylglycerol acetyltransferase (EaDAcT)-expressing line that produced 60 mol% acetyl-TAGs, had no or relatively minor effects on MCFAs accumulation, suggesting fluxes to MCFAs were largely unaltered. Seed germination assays revealed no or minor delays in seed germination for most lines, the exception being CpFatB2 ChFatB2-expressing lines, which had substantially slower seed germination rates. Taken together, these data show that pennycress can be engineered to produce seeds accumulating modest amounts of MCFAs of varying carbon-chain length in TAGs and acetyl-TAGs, with rates of seed germination being delayed in only some cases. We hypothesize that increasing MCFAs further may require functional reductions to endogenous transferases and/or other FA elongases.